2021
DOI: 10.1088/2399-7532/ac2046
|View full text |Cite
|
Sign up to set email alerts
|

A screen-printing method for manufacturing of current collectors for structural batteries

Abstract: Structural carbon fibre composite batteries are a type of multifunctional batteries that combine the energy storage capability of a battery with the load-carrying ability of a structural material. To extract the current from the structural battery cell, current collectors are needed. However, current collectors are expensive, hard to connect to the electrode material and add mass to the system. Further, attaching the current collector to the carbon fibre electrode must not affect the electrochemical properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Most research has used copper foil side strips as contacts, with little consideration having been given to the influence of current collection on device performance. Studies on structural batteries have used screen printing of conductive inks to develop tailored geometries of current collectors [135]. As illustrated in Fig.…”
Section: Current Collectionmentioning
confidence: 99%
“…Most research has used copper foil side strips as contacts, with little consideration having been given to the influence of current collection on device performance. Studies on structural batteries have used screen printing of conductive inks to develop tailored geometries of current collectors [135]. As illustrated in Fig.…”
Section: Current Collectionmentioning
confidence: 99%
“…97,98 Flexural properties have been believed to be important mechanical parameters for structural batteries, because bending is a common deformation state in electric vehicle. 99 Conventional lithium-ion batteries are usually with low flexural modulus around 300 MPa, which results from easy sliding and detaching between electrolyte and electrode layers. 100 In order to prevent sliding effect inside structural batteries, Yang et al reported robust interface between electrode and electrolyte inspired by tree roots, which can stabilize soil and trees against external wind force (Figure 4A).…”
Section: Bio-inspired Tree-root-like Interfacial Design For Stable Li...mentioning
confidence: 99%
“…Structural batteries have become hot research concept in electric vehicle industry owing to high energy density and good mechanical properties, which enable stable power supply under various deformations 97,98 . Flexural properties have been believed to be important mechanical parameters for structural batteries, because bending is a common deformation state in electric vehicle 99 . Conventional lithium‐ion batteries are usually with low flexural modulus around 300 MPa, which results from easy sliding and detaching between electrolyte and electrode layers 100 .…”
Section: Bio‐inspired Structure Design For Robust Interfacesmentioning
confidence: 99%
“…For SPCs, such metal foils are not necessary nor optimal, and alternative current collector architectures which require only partial coverage with metal foil can save significant device mass. 14…”
Section: Introductionmentioning
confidence: 99%